2012
DOI: 10.1063/1.4732100
|View full text |Cite
|
Sign up to set email alerts
|

Inter-tube thermal conductance in carbon nanotubes arrays and bundles: Effects of contact area and pressure

Abstract: We use molecular dynamics simulations to compute junction thermal conductance of carbon nanotubes as a function of crossing angle and pressure, and conductivity of arrays and bundles consisting of multiple junctions as a function of pressure. Two types of arrays are investigated: crossbar structures consisting of alternating orthogonal layers of nanotubes and close-packed bundles of parallel oriented tubes. Conductance of 90° junction increases with pressure 4 fold before saturation; cross-plane thermal conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
67
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 20 publications
7
67
3
1
Order By: Relevance
“…In a random dispersion of CNTs, however, the angle h will take on a range of values. Previous results on different CNT configurations 18 and diameters 10 found that the junction thermal conductance increases as the contact area between the two CNTs increases, which is confirmed by our predictions plotted in Fig. 3 for two different CNT lengths.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…In a random dispersion of CNTs, however, the angle h will take on a range of values. Previous results on different CNT configurations 18 and diameters 10 found that the junction thermal conductance increases as the contact area between the two CNTs increases, which is confirmed by our predictions plotted in Fig. 3 for two different CNT lengths.…”
supporting
confidence: 79%
“…12 Evans et al reached a similar conclusion for two perpendicular (10,10) CNTs in a system with periodic boundary conditions. 10 For a junction built from two parallel (10,10) CNTs separated by 0.8 nm and connected by a third, short (10,10) CNT, Prasher et al 8 found that the thermal conductance between the two parallel CNTs was reduced by an order of magnitude compared to a single perpendicular junction. Such closely spaced junctions are unlikely to be found in low-density CNT networks, but may be present in the packed beds studied by Prasher et al, which have densities on the order of 100 kg/m 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, MD simulations have been successfully used to directly calculate thermal boundary resistance [21][22][23][24][25][26][27] . These studies established the effects of sizes [28][29][30][31] , temperature 21,26,32 , mass differential of the two layers 21,26,27 , lattice mismatch between layers 26,27 , interfacial defects 26,27 , stiffness of the materials, and bond strength at the interface 22,24,32,33 . While the MD data provided knowledge significantly beyond that achieved from analytical models (e.g., the acoustic mismatch model and the diffuse mismatch model 2,9 ), our current understanding of the thermal boundary conduc-tance is far from the material/structure design requirement.…”
mentioning
confidence: 99%
“…Then, the sum of the three CNTs' perimeters is considered as the length of the interface, and 0.335 nm as the thickness. 28,29 The value of A is the product of the length and the thickness of the interface. Energy exchange is carried out per 75 timesteps.…”
Section: Models and Methodologymentioning
confidence: 99%